Pengaruh Pendekatan Joyful Learning Pada Mata Kuliah Muamalah Terhadap Hasil Belajar Mahasiswa FKIP UMSU - Sakinah, Nur; Hasanah, Uswah (Al-Ulum: Jurnal Pendidikan Islam, 2020)
oyful Learning Approach in Muamalah Course Against Student Learning Outcomes of Faculty of Law UMSU that learning is no longer understood merely as a process of transfer of knowledge but must be practiced by students. As a form of implementation of the activities carried out by each student. This study aims to determine whether or not the influence of the problems faced in class is often not in line with expectations. In learning material muamalah students often encounter boredom and difficulty accepting the material. So students feel uncomfortable with learning so that they will do things that can disrupt the learning process.Â This study aims to find out how much the influence of the Joyful Learning approach so that class learning in the implementation of learning should be held interactively, inspiratively, fun, challenging and motivating students to participate actively. Learning is organized in a fun and can have a positive effect on student learning outcomes. The activity carried out by students is conducting classroom practice using a Joyful Learning approach.Â Keywords: Joyful Learning Approach, Learning Outcomes, Muamalah.Â